TP-ellipsis with a polarity particle in multiple-complementizer contexts in Spanish: on topical remnants and focal licensors - Villa-García, Julio (Borealis – An International Journal of Hispanic Linguistics, 2016)
This paper investigates TP-ellipsis in Spanish in the context of multiple-complementizer clauses (i.e., … que XP que ellipsis licensor ellipsis site). The paper argues for a standard ΣP-account of TP ellipsis, with the polarity/focal item (e.g., también/tampoco/sí/no) crucially involved in the licensing of ellipsis. It is argued that the XP-que sequence is hosted in TopicP. The XP is a contrastive topic functioning as the remnant of TP-ellipsis and que is an instance of recomplementation que –a topic marker. The ellipsis licensor, for its part, sits in a CP-related projection that follows TopicP. Given the parallelism drawn here between the items that can partake in the licensing of TP-ellipsis and run-of-the-mill focused phrases, the paper puts forth the claim that ΣP and FocusP should be conflated. Similarly, I explore the relationship established between TopicP (the remnant) and ΣP/FocusP (the ellipsis licensor) in the process of TP ellipsis as well as offer an account of the inability of jussive/optative que to survive ellipsis, unlike recomplementation que.